Essential and Beneficial Trace Elements in Plants, and Their Transport in Roots: a Review - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER, 2017)
The essentiality of 14 mineral elements so far have been reported in plant nutrition. Eight of these elements were known as micronutrients due to their lower concentrations in plants (usually a100 mg/kg/dw). However, it is still challenging to mention an exact number of plant micronutrients since some elements have not been strictly proposed yet either as essential or beneficial. Micronutrients participate in very diverse metabolic processes, including from the primary and secondary metabolism to the cell defense, and from the signal transduction to the gene regulation, energy metabolism, and hormone perception. Thus, the attempt to understand the molecular mechanism(s) behind their transport has great importance in terms of basic and applied plant sciences. Moreover, their deficiency or toxicity also caused serious disease symptoms in plants, even plant destruction if not treated, and many people around the world suffer from the plant-based dietary deficiencies or metal toxicities. In this sense, shedding some light on this issue, the 13 mineral elements (Fe, B, Cu, Mn, Mo, Si, Zn, Ni, Cl, Se, Na, Al, and Co), required by plants at trace amounts, has been reviewed with the primary focus on the transport proteins (transporters/channels) in plant roots. So, providing the compiled but extensive information about the structural and functional roles of micronutrient transport genes/proteins in plant roots.
Keywords: Toxicity; Deficiency; Micronutrient; Beneficial element; Broad range affinity; EFFLUX BORON TRANSPORTER; GENOME-WIDE ANALYSIS; PLASMA-MEMBRANE; METAL TRANSPORTER; IRON UPTAKE; ZIP FAMILY; SILICON TRANSPORTER; GENE FAMILY; FUNCTIONAL-CHARACTERIZATION; REPRODUCTIVE DEVELOPMENT